Protective and causative killer Ig-like receptor (KIR) and metalloproteinase genetic patterns associated with Herpes simplex virus 1 (HSV-1) encephalitis occurrence - Tuttolomondo, Antonino; Di Raimondo, Domenico; Vasto, Sonya; Casuccio, Alessandra; Colomba, Claudia; Norrito, Rosario Luca; Di Bona, Danilo; Arnao, Valentina; Siciliano, Luisa; Cascio, Antonio; Pinto, Antonio (Journal of neuroimmunology, 2020)
The cerebral innate immune system has a critical role in control processes of viral replication in the brain after primary infactivo and immunologic disregulation and inflammation has been reported as a primary determinant of pathogenesis and prognosis of subsequent HSV-1 related encephalitis (HSE). Interaction linking LTR3-activated DCs is also represented by the killer Ig-like receptor (KIR) + pathways on NK cells. Only a few studies analyzed the role of of MMP-9 activity regulating genetic polymorphism on clinical outcome of viral infections. Susceptibility to symptomatic encephalitis depends on SNC viral invasion and BBB disruption. We hypothesize that certain KIR genes and MMP allele may help to characterize a risk profile of developing an acute encephalitis due to HSV 1. Analyze the frequency of KIR genes and the C(−1562)T MMP-9 allels in subjects with HSV-1 encephalitis and to analyze their interaction with regard of the risk of occurrence of a symptomatic encephalitis. Between November 2014 and January 2019, all consecutive patients with symptomatic acute encephalitis were recruited from three wards (Internal Medicine, Neurology, and Infectious Diseases) of “P. Giaccone” University Hospital, Palermo. Patients with acute viral encephalitis in comparison to controls showed a higher frequency AA KIR haplotype, HLA-C2 and of HLA-A-Bw4 alleles. With regard of HLA allele frequency patients with acute viral encephalitis In comparison to controls also showed a higher frequency of HLA-C2 and of HLA-A-Bw4 alleles. With regard of MMP-9 alleles, subjects with acute viral encephalitis were more likely to have the TT genotype. The multiple logistic regression analysis considering variables predictive of the occurrence of acute viral encephalitis showed the detrimental effect of AA KIR, HLAC1, HLA-A-BW4 and HLA-B-BW4T and of TT aplotype of MMP-9 genotype. Our study shows that in immunocompetent adult subjects there is an association between some KIR genes, MMP-9 alleles and HLA-ligand alleles and susceptibility to develop a symptomatic acute viral encephalitis. Definition of the genetic and immunological background of acute viral encephalitis can play a key role to determine personalized medicine. •Certain KIR genes and MMP allele may help to characterize a risk profile of developing an acute encephalitis due to HSV 1.•Patients with acute viral encephalitis showed a higher frequency AA KIR haplotype, HLA-C2 and of HLA-A-Bw4 alleles.•With regard of MMP-9 alleles, subjects with acute viral encephalitis were more likely to have the TT genotype.•At multiple analysis detrimental effect of AA KIR aplptype, HLA-C1, HLA-A-BW4 and HLA-B-BW4T and of TT MMP-9 genotype.•Association between some KIR . HLA and MMP-9 alleles and susceptibility to develop a symptomatic acute encephalitis.